Scope of Periodontium in Forensic Science (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forensic odontology is the application of dental knowledge in forensic science in identification of victims during criminal justice. This article highlights the important role of gingiva and the surrounding periodontal structures in forensic field. Evidence can be collected only with proper documentation of the dental records. The importance of dental records plays a key role not only in identification but also in terms of dental malpractice or in insurance claim. Recent studies have established ante mortem and postmortem changes in gingival and periodontal tissues. Thus periodontitics has a scope in forensic odontology.